STUDY OF FLOATING PHOTOVOLTAIC STRUCTURE TYPES: CONVENTIONAL AND COMPACT - Anjanique, Indira
Solar energy is one of the renewable energy sources that can be utilized in Indonesia to generate electricity using photovoltaic modules. One strategy to save land and increase cooling in the use of solar power plants is to use floating solar power plants that are above the water. Compact structure is a type of floating solar power plant structure with two orientations. This type is different from conventional structures that have only one orientation. Publications related to compact structure are still limited, the majority still discuss the distribution of wind pressure without considering the influence on economic aspects. In this study, compact structure is compared against conventional structures based on energy production and environmental loads. Energy production is obtained using the PVsyst application. Wind loads were simulated using ANSYS Fluent at lake and sea wind speeds validated with the results of other experiments. Loads due to waves and currents are calculated using analytical equations with empirical coefficients based on existing studies. The economic aspect is calculated using Levelized Cost of Energy (LCOE) in four location variations, namely Samboja Reservoir, Tanah Merah Beach, Tilong Dam, and Kelapa Tinggi Beach. The result shows that floating solar power plants with a compact structure type can produce a lower LCOE than conventional structures with a difference of Rp5.66/kWh for 5? tilt angle and Rp9.49/kWh for for 10? tilt angle in the sea near the equator (Tanah Merah Beach and Kelapa Tinggi Beach). Compact structure can minimize wind loads, but with lower power production due to the presence of two different orientations.